Experience of sexual coercion and risky sexual behavior among Ugandan university students - Östergren Per-Olof; Odberg-Pettersson Karen; Agardh Anette (BMC, 2011)
Abstract Background Growing worldwide evidence shows that the experience of sexual coercion is fairly prevalent among young people and is associated with risky sexual behavior thereafter. The causal mechanisms behind this are unclear but may be dependent on specific contextual determinants. Little is known about factors that could buffer the negative effects of coercion. The aim of this study was to assess the association between the experience of sexual coercion and risky sexual behavior among university students of both sexes in Uganda. Methods In 2005, 980 (80%) out of a total of 1,220 students enrolled in Mbarara University of Science and Technology in Uganda participated in a self-administered questionnaire covering socio-demographic and religious factors, social capital, mental health, alcohol use, and sexual behavior. A validated scale of six items was used to assess the experience of sexual coercion. Logistic regression analyses were applied to control for confounders. Potential buffering factors were analyzed by testing for effect modification. Results Fifty-nine percent of those who responded had previously had sexual intercourse. Among the male students 29.0%, and among the female students 33.1% reported having had some experience of sexual coercion. After controlling for age, gender, and educational level of household of origin, role of religion and trust in others sexual coercion was found to be statistically significantly associated with previously had sex (OR 1.6, 95% CI; 1.1-2.3), early sexual debut (OR 2.4, 95% CI; 1.5-3.7), as well as with having had a great number of sexual partners (OR 1.9, 95% CI; 1.2-3.0), but not with inconsistent condom use. Scoring low on an assessment of mental health problems, reporting high trust in others, or stating that religion played a major role in one's family of origin seemed to buffer the negative effect that the experience of sexual coercion had on the likelihood of having many sexual partners. Conclusion The findings of this study suggest that the experience of sexual coercion is common among youth/young adults in Uganda and is subsequently associated with risky sexual behavior in both sexes. The existence of individual and contextual factors that buffer the effects mentioned was also demonstrated. In the Ugandan context, this has implications for policy formulation and the implementation of preventive strategies for combating HIV/AIDS.